Equine placental extract supplement as a night barking remedy in dogs with cognitive dysfunction syndrome. Issue 5 (3rd August 2022) - Amano, Tatsuya; Ikeda, Takashi; Yamaguchi, Makiko; Kakehi, Nobuhisa; Hanada, Keizo; Watanabe, Tsuyuko; Tahara, Kentarou; Hirano, Eiichi
Abstract: With the aging of pet dogs, there has been an increasing trend in senility‐related diseases; additionally, cognitive disorders accompanied by abnormal behaviours are a major burden for owners. Recently, there have been a series of consultations regarding the fact that night barking, which is an abnormal behaviour, remarkably interferes with the owner's sleep and adversely affects the owner's quality of life. However, there has been no effective solution to this problem. In this study, three aged pet dogs diagnosed with dementia were administered an equine placental extract (eqPE) as pet supplement, which has been shown in laboratory models to improve cognitive function. Consequently, night barking ceased 1 week after the administration of eqPE in case 2 and it was observed to decrease in the other two dogs. Furthermore, night barking disappeared 2 and 3 weeks after the administration of eqPE in cases 1 and 3, respectively. No recurrence or exacerbation of night barking was observed in the three cases treated with the eqPE, and no adverse events were observed. These results suggest that eqPE may be useful for improving night barking in pet dogs with dementia, and it is expected to be a new treatment method. Abstract : An equine placenta extract (eqPE) as pet supplement could ameliorate CDS‐associated night barking in three aged pet dogs diagnosed with dementia.